Scaffolding in English Classroom: A Case Study on the Teaching of English Language to Eight-Year Students - Muh. Fadel Fajrin; La Sunra; Hasriani G (PT ARRUS Intelektual Indonesia, 2024)
This study aimed to find out (1) How the teacher perceives the scaffolding strategy. (2) how the teacher applies scaffolding in teaching English. This study used a qualitative descriptive method and collected data through observation and interviews. The observation process was carried out in two meetings in class VIII.6 SMPN 7 Makassar and the interview process was conducted with a teacher. The findings showed that (1) In the interview process, the teacher argues that scaffolding strategies are beneficial in the learning process, namely to build confidence, identify student knowledge, and create student independence. This is very important to achieve learning goals and increase the best potential of each student. (2) The English teacher in class VIII.6 SMPN 7 Makassar uses scaffolding strategy methods in teaching. Researchers found six types of scaffolding strategies used by the teacher in teaching, namely modeling, questioning, giving feedback, breaking down tasks, direct assistance, and providing learning resources. Teacher explain the material to be learned in a structured and systematic manner that can be easily understood by students.